The Urease Inhibitor NBPT Negatively Affects DUR3-mediated Uptake and Assimilation of Urea in Maize Roots - Zanin, Laura; Tomasi, Nicola; Zamboni, Anita; Varanini, Zeno; Pinton, Roberto (Frontiers in Plant Science, 2015)
Despite the widespread use of urease inhibitors in agriculture, little information is available on their effect on nitrogen uptake and assimilation. Aim of this work was to study, at physiological and transcriptional level, the effects of NBPT on urea nutrition in hydroponically grown maize plants. Presence of NBPT in the nutrient solution limited the capacity of plants to utilize urea as a N-source; this was shown by a decrease in urea uptake rate and 15N accumulation. Noteworthy, these negative effects were evident only when plants were fed with urea, as NBPT did not alter 15N accumulation in nitrate-fed plants. NBPT also impaired the growth of Arabidopsis plants when urea was used as N-source, while having no effect on plants grown with nitrate or ammonium. This response was related, at least in part, to a direct effect of NBPT on the high affinity urea transport system. Impact of NBPT on urea uptake was further evaluated using lines of Arabidopsis overexpressing ZmDUR3 and dur3-knockout; results suggest that not only transport but also urea assimilation could be compromised by the inhibitor. This hypothesis was reinforced by an over-accumulation of urea and a decrease in ammonium concentration in NBPT-treated plants. Furthermore, transcriptional analyses showed that in maize roots NBPT treatment severely impaired the expression of genes involved in the cytosolic pathway of ureic-N assimilation and ammonium transport. NBPT also limited the expression of a gene coding for a transcription factor highly induced by urea and possibly playing a crucial role in the regulation of its acquisition. This work provides evidence that NBPT can heavily interfere with urea nutrition in maize plants, limiting influx as well as the following assimilation pathway.